2019
DOI: 10.1177/1758155919848229
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in the application of non-invasive genetic sampling to study Neotropical birds: Uses, goals, and conservation potential

Abstract: The non-invasive collection of biological samples has proven useful to study a diverse array of research topics worldwide. Here, we present a systematic bibliographical synthesis exploring how the non-invasive collection of genetic samples has been used to study avian populations in the Neotropics. We searched international online databases for scientific publications, spanning from 2007 to 2017, to describe the trends and identify the sample types used, species studied, and research questions addressed. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…For many rare or elusive species, specimens of opportunity may be the most effective way to fill these knowledge gaps, and for some species they may be the only source of reliable knowledge (Robbirt et al 2011, Roberts et al 2016. Specimens of opportunity, such as salvaged carcasses and museum specimens, have proved essential in identifying new species, clarifying a species' range and population structure, and in retrospective analyses of biodiversity (Newbold 2010, Holmes et al 2016, Baus et al 2019, Coombs et al 2019, Schwartz et al 2020. As many museums and research institutions face financial pressure to justify maintenance and upkeep of research collections, it is increasingly important to highlight the value of these collections to wildlife and conservation studies.…”
Section: Introductionmentioning
confidence: 99%
“…For many rare or elusive species, specimens of opportunity may be the most effective way to fill these knowledge gaps, and for some species they may be the only source of reliable knowledge (Robbirt et al 2011, Roberts et al 2016. Specimens of opportunity, such as salvaged carcasses and museum specimens, have proved essential in identifying new species, clarifying a species' range and population structure, and in retrospective analyses of biodiversity (Newbold 2010, Holmes et al 2016, Baus et al 2019, Coombs et al 2019, Schwartz et al 2020. As many museums and research institutions face financial pressure to justify maintenance and upkeep of research collections, it is increasingly important to highlight the value of these collections to wildlife and conservation studies.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying DNA collection methods that minimize mortality and disruption to organisms is important when the taxa being studied are rare or are of high conservation priority [6][7][8][9][10]. Our results demonstrated that both swabbing and tissue biopsy collection…”
Section: Discussionmentioning
confidence: 78%
“…In addition, SSR is still the most widely used genetic marker in forensic identifications and noninvasive genetic studies of endangered species from degraded samples owing to its low quantity/quality DNA template demand and high reproducibility results (Lampa et al, 2013; Willows‐Munro & Kleinhans, 2020). We can acquire sufficient DNA for SSR genotyping even in degraded samples such as eggshells, feathers, and feces (Baus et al, 2019). Furthermore, a strong background in computing skills and bioinformatics is needed to deal with the large quantity of SNPs, whereas researchers can complete SSR analyses with limited computing skills on a laptop computer (Hodel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%